Studying the rheological properties of poly(vinyl pyrrolidone) in chloroform solutions - Marwa S. Al-howach, Zaineb O Ettarhouni, Abdulhakim A. Jangherb (Journal of Pure & Applied Sciences, 2020)
Three molecular weights (25k, 44k and 700k) of Poly(vinyl-pyrrolidone), PVP solutions in chloroform have been studied to conduct some of their rheological properties. In the temperature range of (25 - 45°C). Density and flow time parameters have been measured and used to calculate the viscosity parameter. The collected viscosity data suggests the ideal behaviour in the low concentrations of PVP solutions, due to the reduction of the interaction forces between molecules. However, the viscosity of higher concentrations is strongly affected by changing the molecular weight rather than the concentration itself. In addition, the density, flow time and viscosity parameters of 700K are more influenced by the temperature change, than the other two molecular weights.